Effects of various uterine treatments on calving-to-conception interval - Kiracofe, G.; Brower, G.R.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
Cows were given intrauterine infusions of enzymes, antibacterials, bacteria, or a combination of enzymes and antibacterials after calving to study basic changes in the post-partum uterus and effect on rebreeding. The group given nitrofurazone, an antibacterial compound, had the highest conception rate; however, calving-to-conception interval was lengthened. Combining proteolytic enzymes with the nitrofurazone gave an intercal to conception similar to that of control cows. Nitrofurazone caused this uterine lining to erode. Combining enzymes with nitrofurazone prevented some of the erosion. Innoculating the uterus with bacteria (Lactobacillus acidophilus) after calving did not affect the calving-to-conception interval.
Keywords: Beef; Nitrofurazone; Antibacterials; Conception